O papel dos Klesas no contexto moderno do Ioga no Brasil: uma investigação sobre os possíveis deslocamentos da causa do mal e da produção de novos bens de salvação por meio da fisiologia biomédica ocidental - Simões, Roberto Serafim (2015)
The ancient yoga period emerges amid a stratified Indian society and influenced by religions like samkhya and the Brahmanical Hinduism if systematizing it as an orthodox Hindu darśana through ancient scripture Yoga Sutras (IS) some centuries before the Christian era. The IS explains both the causes of human suffering and the promise of a good yogi life, based on the behavioral theory of klesas (attachment, aversion, fear of death, pride and ignorance) as adverse spiritual evolution. An eightfold path or asthanga yoga (AI) is built-from it as the yogic proposal for salvation of the soul. The AI aims, through ethical conduct, practices corporal rituals and mystical experience of samadhi mitigate klesas seeking union with God/Isvara. On average Indian age, between X-XV centuries AD, this system of yogic beliefs is the Tantric religiosity, Jain and Buddhist raising the body's value over the other doctrinal aspects of IS. The modern phase of yoga, however, is being erected under the influence of a new social - religious context . Currently, more than Brahmins and swamis , yoga seeks its legitimacy as spiritual path under the aegis of scientific rationality and new religious movements in the West . In this process , the yoga reframes its mystical language circulating among ashrams and Indian forests of ancient and medieval times to an audience facing the stressful challenges of living in large Western cities, above all, a society of consumption, secular and privatized religiously. It is known that nowadays the yoga reframes its metaphysical physiology in the light of biomedical science , I suspect that the theory of klesas , may be going through a religious reform as well. In order to understand these possible soteriological transformation of the current yoga, I led 13 semi-structured interviews with ten way yogis and three Brazilian scientists psychobiological area investigating the yogic system acts as therapy and healing. The data revealed a cleavage perception in the modern yoga, between belonging to a therapeutic New Age or more a Western biomedical technique. From this juncture new beliefs emerged to legitimize the discourse yoga against the socialreligious situation in which it now lives. More than just symbolic reframing, modern yogic soteriology is passed today by a salvific transformation process. The main changes that stood out are: 1) the elevation of design stress level of klesa or spiritual obstacle; and 2) the relaxation antagonistic to stress-klesa, achievement mystical nature of samadhi; and 3) consequently, salvation/liberation of klesas-stress acquire substance "empirical" an unchanging spiritual state of no stress or a kind of "divine homeostasis." It is concluded that scientific rationality rather than promote religious yoga disenchantment, it legitimizes it as a new system of beliefs and produces new goods of salvation (stress-klesa, relaxation-samadhi and homeostasis-kaivalya) . The association of the health benefits of yoga practices defended and propagated by biomedical physiology associated with the restlessness of the western urban centers , may have weakened the behavioral theory of klesas as essential cause of human suffering